Transition of Care of the Spina Bifida Patient from Childhood to Adulthood - Tomei, Krystal L; Zhou, Xiaofei (Journal of Pediatric Neurology, 2020)
Spina bifida is a complex disease process, the care of which involves multiple physicians and other healthcare providers in several disciplines. As our treatment of this disorder has improved over time, thus has survival of these patients into adulthood. Consideration in the care of young adults and adults with spina bifida poses significant challenges that parallel many other disease processes of childhood where medical advances have improved survival. We attempt to discuss the complex disorder that is spina bifida and some of the challenges associated with transition of care of these patients into adulthood.
Keywords: spina bifida transition; myelomeningocele; transition of care